Pi Pulsations and Associated Phenomena in the Auroral Region - Masayuki KUWASHIMA (National Institute of Polar Research, 1979)
Concurrent observations of the geomagnetic vaiiations by means of a fluxgate magnetometer and an induction magnetometer were carried out at Syowa (-66.7゜, 72.4° in corrected geomasnetic coordinates) and Mizuho Stations (-68.7°, 72.9°in corrected geomagnetic coordinates) in Antarctica during the period from August 29 to September 29, 1973, by the 14th Japanese Antarctic Research Expedition. In association with the substorm onset, expansion and recovery phases, various kinds of Pi pulsations were observed at the two stations. In the present paper, preliminary results of the Pi 2 and Pi (c) pulsations are reported. The Pi 2 period is closely associated with the auroral breakup position in the following way that it becomes shorter (longer) when the auroral breakup occurs at lower (higher) latitude. In association with Pi (c), the substorm associated Pc 3 are observed at Syowa and Mizuho Stations.